2015
DOI: 10.1063/1.4937276
|View full text |Cite
|
Sign up to set email alerts
|

Broadband ultra-high transmission of terahertz radiation through monolayer MoS2

Abstract: In this study, terahertz (THz) absorption and transmission of monolayer MoS 2 was calculated under different carrier concentrations. Results showed that the THz absorption of monolayer MoS 2 is very small even under high carrier concentrations and large incident angle. Equivalent loss of the THz absorption is the total sum of reflection and absorption that is one to three grades lower than that of graphene.The monolayer MoS 2 transmission is much larger than that of the traditional GaAs and InAs two-dimensiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…However, there was no report on terahertz damage on MoS 2 . Theoretical simulations indicated that the THz absorption of mono-layer MoS 2 was very low and the maximum THz absorption of mono-layer MoS 2 was approximately 5% [151]. The sum of reflection and absorption losses of mono-layer MoS 2 was lower than that of graphene by one to three orders of magnitude.…”
Section: Terahertz Wave Irradiationmentioning
confidence: 95%
“…However, there was no report on terahertz damage on MoS 2 . Theoretical simulations indicated that the THz absorption of mono-layer MoS 2 was very low and the maximum THz absorption of mono-layer MoS 2 was approximately 5% [151]. The sum of reflection and absorption losses of mono-layer MoS 2 was lower than that of graphene by one to three orders of magnitude.…”
Section: Terahertz Wave Irradiationmentioning
confidence: 95%
“…1,29,30 The carrier concentration on the order of 10 12 cm −2 in MoS 2 has been reported 31 and it can be increased to be an order of magnitude larger via doping or gating. 31,32 The estimated carrier concentration is 2 or 3 orders of magnitude smaller than the density of valence electrons (2.6 × 10 16 cm −2 ) in the monolayer CrI 3 such that the electronic structure can hardly be influenced by the occupation of these carrier. This fact justifies our estimation of carrier concentration based on the calculated DOS of neutral systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the polarization and electrode arms are parallel, the transmission is strongly suppressed. This limitation could be eliminated by the introduction of a DC conductive (but THz transparent) material for the electrode, such as MoS 2 . This would allow the device to operate under large angles of incidence as shown and would also make the response independent of azimuthal polarization angle.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation could be eliminated by the introduction of a DC conductive (but THz transparent) material for the electrode, such as MoS 2 . 47,48 This would allow the device to operate under large angles of incidence as shown and would also make the response independent of azimuthal polarization angle. fairly frequency independent from THz to infrared.…”
Section: Angle Of Incidencementioning
confidence: 99%